A combined topical therapy of chronic dermatoses - N. N. Filimonkova; YE. A. Bakhlykova! (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article analyzes literature sources on the etticacy ot the topical glucocorticosteroid therapy ot chronic dermatoses. Special attention is paid to evidence-based studies ot the etticacy and satety ot a combination therapy ot complicated chronic dermatoses using the Akriderm GK drug.